2017
DOI: 10.18203/issn.2454-5929.ijohns20175606
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tympanic membrane perforation and conductive hearing loss in patients with chronic otitis media

Abstract: INTRODUCTIONThere is high incidence of conductive hearing loss caused by perforations of tympanic membrane in chronic otitis media. The results of studies regarding the effect of the size and the site of perforations on the degree of hearing loss conflicting.Some studies show a correlation between degree of hearing loss and the size of tympanic membrane perforation that larger perforation causes larger hearing loss.1-4 The weak point of these studies is the crude estimation of the size of tympanic membrane per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Moreover, all the perforations were dry. 21 Posterior Normal Hearing 1(Ali et al 2019) 22 Anterior Normal Hearing 1(Ali et al 2019) 22 Multiple Moderate 1(Gupta et al 2019) 28 Total Mild 1(Gupta et al 2019) 28 Though it was found that most of the studies established mild degree hearing loss with most of the sites of perforations but looking at the individual intensities in decibels, posterior perforations had greater hearing loss than anterior ones. The studies that discussed central perforations depicted that central one had greater hearing loss than anterior and posterior perforations.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all the perforations were dry. 21 Posterior Normal Hearing 1(Ali et al 2019) 22 Anterior Normal Hearing 1(Ali et al 2019) 22 Multiple Moderate 1(Gupta et al 2019) 28 Total Mild 1(Gupta et al 2019) 28 Though it was found that most of the studies established mild degree hearing loss with most of the sites of perforations but looking at the individual intensities in decibels, posterior perforations had greater hearing loss than anterior ones. The studies that discussed central perforations depicted that central one had greater hearing loss than anterior and posterior perforations.…”
Section: Resultsmentioning
confidence: 99%
“…Fidan et al ( 2020 ) reported hyperaemia and bulging of the tympanic membrane, while in a case series by Dharmarajan et al ( 2021 ), four participants presented with retracted tympanic membrane and two had dull tympanic membranes. While the third study (Wanna et al, 2020 ) did not specifically report on the anatomical structure of the tympanic membrane, this case study reported that a participant presented with purulent otorrhea, which may be indicative of tympanic membrane perforation (Ali & Alshareda, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of increasing the surface area ratio of the tympanic membrane to the oval window increases sound pressure by about 27 decibels while the movement of the ossicle lever contributes about 3 dB. 14 Ali et al 20 reported that a conductive hearing impairment in the tympanic membrane perforation could be resulted from two processes. There is ossicular coping that caused a pressure difference between the tympanic membrane surfaces on the inside and outside which would cause a decrease in phase between oval and round windows, and the surface of the tympanic membrane was subjected to interference with the transmission of sound waves from the external auditory canal-ossicles-cochlea.…”
Section: Discussionmentioning
confidence: 99%